Chronic atrophic gastritis as a precancer: the evolution of ideas from the Sydney consensus to Maastricht VI - Yu. M. Stepanov; Yu. A. Haidar; O. A. Maltseva (Patologìâ)
Aim. The purpose of the work is the evolution of systems and classifications of gastritis: Sydney Consensus (1990), Houston Modification (1994), OLGA/OLGIM (2008), Kyoto (2014), MAPS II (2019), Maastricht IV (2022).